SELF-ASSESSMENT OF MENTAL AND PHYSICAL HEALTH AS THE EFFECT OF THREE MONTHS OF RECREATIONAL TREATMENT OF WOMEN - Nevres Muminović,; Osman Lačić,; Jasmin Bilalić,; Tarik Huremović,; Mensur Halilovic, (Sport Scientific And Practical Aspects, 2025)
The primary objective of this study is to analyze the self-assessment of the mental and physical health of young women from the effects of programmed recreational activities in a three-month period. The sample is composed of 35 women (20 - 40 years old). For a sample of variables in the assessment of mental and physical health, standardized instruments were used: THE HAD scale - Hospital Anxiety and Depression Scale (for mental health assessment) and EQ thermometer (for physical health assessment) The results of the overall condition of all participants before the start of the experimental procedure, 24 participants had no symptoms of depression, 8 participants had a borderline condition, and 3 participants with depressive disorder. After three months of recreational treatment, 30 of the participants have no symptoms of depression, 3 participants have borderline condition and 2 participants with depressive disorder. When it comes to the self-assessment of anxiety in the initial state, it was noted that 26 participants of the experiment had no signs of anxiety, 6 participants had a borderline state of anxiety, while 3 participants had anxiety disorders, of which 2 participants slightly above the limit state and one participant with a particularly high number of points indicating a more severe state of anxiety. At the end of the experiment, 31 participants had no signs of anxiety, 4 had a borderline state and 1 person with a severe anxiety condition. Before the start of recreational activities, one participant rated their physical health as extremely poor and 3 people rated their health as poor. The largest number of participants before the experiment, 16 of them, rated their physical health slightly above average, 10 women rated their physical health as excellent and 5 women rated themselves the best imaginable physical health. After the experiment, only 4 participants estimated lower and average self-health, above average 6, 20 women claimed to have excellent health and 5 participants in the experiment claimed to be in the best physical health imaginable.